1998
DOI: 10.1002/(sici)1099-1085(19980630)12:8<1197::aid-hyp612>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Using Lagrangian particle saltation observations for bedload sediment transport modelling

Abstract: A Lagrangian model for the saltation of sand in water is proposed. Simulated saltation trajectories neglecting particle rotation and turbulence eects compare fairly well with experimental observations. The model for particle motion is coupled with a stochastic model for particle collision with the bed, such that a number of realizations of the saltation process can be simulated numerically. Model predictions of mean values and standard deviations of saltation height, length and streamwise particle velocity agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 31 publications
3
89
0
Order By: Relevance
“…6 and 7 herein, we compare numerical results obtained with our code [4,17,18] against data collected by [32,34], for the cases of gravels and sands moving in saltation, respectively. Results indicate that whereas the Basset force is negligible for the range of sizes of gravels moving as bed-load [33], the force becomes very important for sands [35]. In the latter case, the length of a single particle jump can be under-predicted by about 40 % if the force is omitted, and the jump height can be under-predicted by about 15 % [4].…”
Section: Rate Of Convergence and Accuracymentioning
confidence: 96%
See 2 more Smart Citations
“…6 and 7 herein, we compare numerical results obtained with our code [4,17,18] against data collected by [32,34], for the cases of gravels and sands moving in saltation, respectively. Results indicate that whereas the Basset force is negligible for the range of sizes of gravels moving as bed-load [33], the force becomes very important for sands [35]. In the latter case, the length of a single particle jump can be under-predicted by about 40 % if the force is omitted, and the jump height can be under-predicted by about 15 % [4].…”
Section: Rate Of Convergence and Accuracymentioning
confidence: 96%
“…However, it has been recently found that the Basset force becomes important when the particles are relatively small [4,35] as follows. In Figs.…”
Section: Rate Of Convergence and Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of a particle undergoing bedload transport has been estimated between 1/4 and 1/7 of the depth-averaged flow velocity (Bilgili et al 2003;Bogardi 1974). A more rigorously derived formula by Niño and García (1998) is based on experimental and numerical analyses that relate the dimensionless streamwise particle velocity, u s , to the dimensionless bed shear, τ * .…”
Section: Jump Lengthmentioning
confidence: 99%
“…Therefore, the mean grain size and density of the sediment are used to calculate the average particle speed rather than that of the individual bivalves. The model results presented here use this formulation of jump length and parameter estimates derived by Niño and García (1998). These empirical estimates indirectly depend upon the critical shear stress of the sediment (critical erosion velocity of site 1 sediment 1.65 cm s −1 ; Hunt unpubl.…”
Section: Jump Lengthmentioning
confidence: 99%